JUUL's 2019 Removal of Mint-Flavored Pods and Changes to the Retail Environment of Electronic Nicotine Delivery Systems in Florida and the United States. Issue 11 (15th May 2022) - Gaber, Jennifer; Gammon, Doris G; Lee, Youn Ok; Nonnemaker, James; Young, Brittany; Kim, Annice; Porter, Lauren
Abstract: Introduction: The increase in youth electronic nicotine delivery system (ENDS) use coincided with JUUL's rapid rise, which prompted investigations and lawsuits aimed at this leading brand. In response, JUUL discontinued sweet flavors in late 2018, followed by mint flavors in November 2019. We assessed ENDS sales and prices at both the state and national level before and after JUUL's removal of mint flavors. Aims and Methods: Nielsen retail sales data on ENDS products from convenience and food stores in 4-week aggregates were analyzed between January 2019 and January 2020 in Florida and the United States. Standardized units were created. Unit market share and growth rates were calculated for top brands and flavors in the periods before and after JUUL's mint removal. Average prices within brand and product type were calculated. Results: Following JUUL's removal of mint in November 2019, JUUL's market share dropped from over 66% in Florida and the United States to 37.1% (Florida) and 55.1% (United States). In January 2020, the second leading brands were Puff Bar (15.0%) in Florida and Vuse (18.1%) in the United States. Mint market share decreased and share of all other flavor categories increased, particularly menthol and concept. Total ENDS sales increased in Florida but decreased in the United States. Average prices of ENDS devices decreased. Conclusions: While JUUL's actions led to a decline in its sales, Puff Bar emerged and menthol and concept flavors experienced growth. Findings also demonstrate how changes by influential brands differentially affect purchase patterns at the national and state level. Implications: These findings support the growing body of evidence that tobacco industry self-regulation, with selective flavor removal by the leading ENDS brand in this case, is insufficient to reduce total ENDS sales, including sales of flavored products which are preferred by youth. Results suggest that brand and flavor substitution compensated for the removal of mint JUUL pods. Understanding changes to the ENDS market in response to industry actions, at both the state and national level, can inform future regulation and interventions. These findings can also inform efforts to prevent and reduce youth ENDS use.